Easy Flower : flowers meet business and technology - Jie, Jiao; Ziqian, Zhao; Jiulu, Zhang; Haipeng, Xu; Yuanshen, Gao; Binhai, Zhu; Chi, Ma; Yanyang, Wang (London : Tsinghua University School of Economics and Management, 2020)
In less than four years, Easy Flower (EF) grew from an e-commerce flower retail start-up to China's largest supply chain operator in fresh flowers. Easy Flower positioned itself as a provider of quality flowers to retail florists. Taking advantage of its strength in technology talent, and pooling its finances, the company successfully created a national distribution infrastructure network, disrupting and transforming the fractured supply chain system of China's flower industry and dramatically enhancing its supply chain efficiency. Having built an industry leader from scratch, founder Rong Chao had to think about Easy Flower's future strategy. In late 2018, he saw two options: further integrating the flower value chain in China, or internationalizing his business by exporting components of his technology and systems to flower platforms in other countries. Constrained by the company's resources, he had to assess the various risks and requirements that each direction would entail.
Originally Published InJie, J., Ziqia, Z., Jiulu, Z., Haipeng, X., Yuanshen, G., Binhai, Z., Chi, M., & Yanyang, W. (2020). Easy Flower: Flowers Meet Business and Technology. 1-719-231. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic commerce -- China -- Case studies